Fundamental investigations into the factors affecting the response of laccase-based electrochemical biosensors - Fogel, Ronen (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
Given their widespread effects and distribution in both natural and industrial environments, the monitoring of phenolic compounds is of considerable analytical interest. Electrochemical biosensor technologies, in particular those comprising laccase enzymes, afford many potential benefits to address this analytical need. However, several key factors affecting sensor response currently limit their applicability. This Thesis reports on the fabrication and optimisation of an electrochemical laccase-based biosensor towards the application of the monitoring of phenolic compounds. Selected factors considered to affect sensor response were investigated using the optimised biosensor. These included: electrochemical, biochemical and substrate-dependent factors, which were found to intersect in modulating biosensor response signals. Through the application of transducer-dependent and substrate-dependent parameters, the selective and simultaneous detection of a mixture of different phenolic analytes is successfully demonstrated. This Thesis also investigates the use of Quartz-Crystal Microbalance with Dissipation (QCM-D) technology, an analytical technique that measures physical parameters of thin-film structures, towards the successful monitoring of enzyme immobilisation strategies. These strategies are fundamental to the successful fabrication of biosensors, and the real-time monitoring of immobilised film formations is of considerable research interest. In the studies reported on in this Thesis, QCM-D technology was demonstrated to be an effective complementary technology in the prediction of film immobilisation techniques on the resultant biochemical kinetics of immobilised enzymes.
Keywords: Laccase; Phenols; Biosensors